2021
DOI: 10.1002/mus.27337
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for genetic testing of muscle and neuromuscular junction disorders

Abstract: Despite recent advances in the understanding of inherited muscle and neuromuscular junction diseases, as well as the advent of a wide range of genetic tests, patients continue to face delays in diagnosis of sometimes treatable disorders. These guidelines outline an approach to genetic testing in such disorders. Initially, a patient's phenotype is evaluated to identify myopathies requiring directed testing, including myotonic dystrophies, facioscapulohumeral muscular dystrophy, oculopharyngeal muscular dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 227 publications
(556 reference statements)
0
3
0
Order By: Relevance
“…However, should the genetic panel fails to detect pathogenic variants, or if a mitochondrial myopathy is initially suspected, then EDX testing should be considered as it could reveal an underlying myopathy, help target muscle biopsy site, and guide further evaluation. If a mitochondrial myopathy is present, a muscle biopsy would provide affected tissue for high‐yield diagnostic mitochondrial DNA sequencing 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…However, should the genetic panel fails to detect pathogenic variants, or if a mitochondrial myopathy is initially suspected, then EDX testing should be considered as it could reveal an underlying myopathy, help target muscle biopsy site, and guide further evaluation. If a mitochondrial myopathy is present, a muscle biopsy would provide affected tissue for high‐yield diagnostic mitochondrial DNA sequencing 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…Potentially relevant studies were subsequently screened by full text reading, with any possible conflicts resolved by discussion and reaching a consensus. Studies included in the systematic review met the following inclusion criteria: a) Diagnosis of MD based on guidelines for genetic testing of muscle and neuromuscular junction disorders [ 27 ], or any other definition claimed by original studies’ authors; b) At least one of the following plasma/serum levels of lipids was reported: triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL); c) Same data in non-muscular dystrophic population were reported; d) English only. Studies were excluded if: a) No clear diagnosis of MD was reported; b) Animal or in vitro studies; c) No report or measures of plasma/serum levels of lipids was reported; d) Absence of non-MD ‘healthy’ control lipid values, which is a requirement for meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…repeats, highly homologous regions, and regions of high and low GC content ( 37 ). Common neuromuscular repeat expansion disorders not detectable via NGS include myotonic dystrophy 1 and 2, facioscapulohumeral muscular dystrophy 1 (FSHD1), oculopharyngeal muscular dystrophy (OPMD), oculopharyngodistal myopathies ( 52 ), and C9orf72 -related amyotrophic lateral sclerosis. When ordering a gene panel, it is thus essential to check if the gene panel included the appropriate methodology to cover these special conditions.…”
Section: Disadvantages Of a Gene Panelmentioning
confidence: 99%
“…Eg. in a patient with muscle weakness, genes for Pompe Disease, Congenital Myasthenic Syndrome ( 52 ), and Spinal Muscular Atrophy ( 86 ) should be included to avoid missing a potentially treatable disease.…”
Section: How To Choose a Good Quality Gene Panelmentioning
confidence: 99%